Reproductive Parameters of Mangalarga Marchador Mares in a Commercial Embryo Transfer Programme - Lopes, E. de P.; Siqueira, J. B. [UNESP]; Pinho, R. O.; Guimaraes, J. D.; Rocha, A. N.; de Carvalho, G. R.; Torres, C. A. A. (Wiley-Blackwell, 2011)
ContentsThe objective of this study is to evaluate the reproductive efficiency in donors and recipient Mangalarga Marchador mares in commercial programmes of embryo transfer (ET) and the effects of some reproductive characteristics and ET methodology on conception rates in the recipient mares. A total of 1140 flushing procedures were performed and 830 embryos (72.8%) were recovered. There were no differences between the rates of embryonic recovery in the different breeding seasons (p > 0.05) and 92.8% of the recovered embryos were 8-9 days old. There was no difference in the embryonic recovery regarding the collection order from the first to the ninth embryo collection along the breeding season, as well as among mares inseminated during the foal heat or subsequent cycles (p > 0.05). Pregnancy rates observed in the total period of all reproductive seasons at 15, 30, 45 and 60 days of pregnancy were 73.4, 69.9, 66.7 and 64.5%, respectively. Differences in pregnancy rate and early embryonic loss rates were not observed between embryos transferred immediately after collection (66.8% and 13.5%) and embryos transported at room temperature for periods of < 1 h (62.9% and 14.4%; p > 0.05). Pregnancy rates were higher when the interval between ovulations of donor and recipient mares remained between -3 and -2 days (p < 0.05), and the lowest rates were observed for intervals of -6 days (p < 0.05) with intermediary values for intervals of -1, 0 and +1 (p > 0.05). Embryonic loss rates, however, did not differ between intervals of ovulation's synchronism between donor and recipient mares (p > 0.05). This flexibilization in the ovulatory synchronism between donor and recipient mares optimizes the use of recipient mares, thus reducing costs and facilitating management of horse breeding farms.